The Role of Mother in Education as Reflected Iwan Setya-wan’s Novel 9 Summers 10 Autumns - Adang Ridwan; Ria Karmila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study investigates the educational role of a mother in Iwan Setyawan’s Novel 9 Summers 10 Autumns. The research addresses three main problems: (1) How does the mother prioritized family needs in 9 Summers 10 Autumns novel a translated by Maggie Tiojakin (2) How does the role of mother to create children’s educations in 9 Summers 10 Autumns novel a translated by Maggie Tiojakin. Using a qualitative approach, data were collected through documentation. The data collection process in this research involves identified, classified, analyzed, and organized systematically to support the completion of the research. The data were analyzed through identification, classification, description, and interpretation. The findings reveal that she manages household needs with precision, provides warmth and security, and remains strong despite her husband's imprisonment. Her modest home, though small, becomes a place filled with love, simplicity, and gratitude. Her sacrifices selling belongings and borrowing money reflect her unwavering dedication to her family’s survival and harmony. Her commitment to education is shown through her tireless support, never letting her children work, and always encouraging them to study and succeed. Her love and sacrifices result in her children graduating from university and eventually improving the family’s quality of life. The novel illustrates the power of maternal love, perseverance, and the profound impact of a mother’s role in shaping her children’s future.